Exports and Employment in Indonesia: The Decline in Labor-Intensive Manufacturing and the Rise of Services - Haryo Aswicahyono; Douglas H. Brooks; Chris Manning (Asian Development Bank (ADB), 2011)
Employment generation has been a challenge in Indonesia since the Asian financial crisis, especially in labor-intensive manufacturing. Drawing on work by James and Fujita (2000), this paper examines the impact of exports on jobs, based on an analysis of input–output tables over the period 1995–2005. It finds that fewer jobs were created through exports in manufacturing industries in 2005 than before the crisis, because of slower growth in manufacturing exports and a shift away from light industry. The slowdown is potentially costly due to the endemic elastic supply of unskilled labor. However, there was an increase in jobs in the services sector, partly because of indirect connections with the main export industries. This could be enhanced through greater domestic and international competition in services. The main constraints to job creation through exports appear on the supply side, especially those related to poor infrastructure, an uncertain investment climate, and tight labor regulations.
hdl:11540/1997
Keywords: 330; Export; Industrie; Beschäftigungseffekt; Input-Output-Analyse; Indonesien